Role of education and culture in social development - Singh Farswan, Digar (Journal of Social Review and Development, 2023)
Social development is the development of social and emotional skills across the lifespan with particular attention to childhood, adolescence, and the interaction with school and education. Healthy social development allows people to form positive relationships with family, friends, teachers, and other people in their lives. Social development involves learning the values, knowledge, and skills of social interaction. In this process, learners will learn communication and interaction with teachers, other learners, and friends in a school environment. Social and emotional skills are passed on to children directly by those who care for and teach them, as well as indirectly through social relationships within the family or with friends. Also, through children’s participation in the culture around them and after-school clubs or after-school sports. Social, as well as individual development, takes place in certain cultural contexts. It is affected by culture and it affects culture. There is constant mutual interaction between culture and social development, whether it is prearranged and carefully designed or spontaneous and unintentional. The evidence of cultural impact on social development can be found in many different areas of social life. Starting from early childhood education, when art and culture play a crucial role in developing young children’s creativity, basically through all levels of formal and informal education, ending with intergenerational and lifelong learning programs. In fact, culture and creativity are necessary elements for personal development as well as social development.